2021
DOI: 10.1111/ijcp.14552
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of apixaban versus enoxaparin in preventing wound complications and deep venous thrombosis following total knee replacement surgery: A retrospective study

Abstract: Deep venous thrombosis (DVT), which is the formation of a blood clot (thrombus) in the veins, is a life-threatening condition caused mainly by vascular injuries, immobility, and hypercoagulation. 1 It can complicate the outcomes of patients who have undergone orthopaedic surgeries, such as for a total knee replacement or total hip replacement, especially in elderly patients who are more prone to long periods of immobility after surgery and injury. 2,3 Falck-Ytter et al 4 estimated a 5%-22% DVT incidence follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…API, an oral antithrombotic preparation, comparable to enoxaparin is suitable for both knee replacement and HA patients, effectively reducing the incidence of DVT and the risk of postoperative bleeding [19,20] . Enoxaparin, is a kind of LMWH that can only be administered subcutaneously, can inhibit FXa by binding to antithrombin, thus playing an antithrombotic role [21] .…”
Section: Resultsmentioning
confidence: 99%
“…API, an oral antithrombotic preparation, comparable to enoxaparin is suitable for both knee replacement and HA patients, effectively reducing the incidence of DVT and the risk of postoperative bleeding [19,20] . Enoxaparin, is a kind of LMWH that can only be administered subcutaneously, can inhibit FXa by binding to antithrombin, thus playing an antithrombotic role [21] .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, advanced age was found to be a risk factor for lower extremity DVT after total knee arthroplasty. It has been shown [ 18 , 19 ] that elderly patients have degenerative changes in vascular elasticity due to the decline in blood circulation function, leading to a subsequent decrease in the body ability to dissolve fibrin, slowing down or even stagnation of blood flow, which is thought to be closely related to the occurrence of DVT. Therefore, increased attention should be paid to elderly patients.…”
Section: Discussionmentioning
confidence: 99%